2017
DOI: 10.1177/1460458217723170
|View full text |Cite
|
Sign up to set email alerts
|

Mobile three-dimensional visualisation technologies for clinician-led fall prevention assessments

Abstract: The assistive equipment provision process is routinely carried out with patients to mitigate fall risk factors via the fitment of assistive equipment within the home. However, currently, over 50% of assistive equipment is abandoned by the patients due to poor fit between the patient and the assistive equipment. This paper explores clinician perceptions of an early stage three-dimensional measurement aid prototype, which provides enhanced assistive equipment provision process guidance to clinicians. Ten occupat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 48 publications
0
17
0
4
Order By: Relevance
“…Following review of 67 full-text papers, 14 studies met the inclusion criteria. These 14 studies were reported in 16 articles as presented in Table 1 (Atwal et al, 2013 andMoney et al, 2011 described the same study, as did Hamm et al, 2017a and2017b). Figure 1 shows the PRISMA chart summarising the search and study selection process.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following review of 67 full-text papers, 14 studies met the inclusion criteria. These 14 studies were reported in 16 articles as presented in Table 1 (Atwal et al, 2013 andMoney et al, 2011 described the same study, as did Hamm et al, 2017a and2017b). Figure 1 shows the PRISMA chart summarising the search and study selection process.…”
Section: Search Resultsmentioning
confidence: 99%
“…The 3D-MAP program is a mobile application that draws on three-dimensional visualisation technology and aims to facilitate services users to record measurements within the home as part of the assistive equipment provision process (Hamm et al, 2017a(Hamm et al, , 2017b). Hamm and colleagues conducted surveys and focus groups with healthy adults (aged over 50 years) (Hamm et al, 2017a) and Evaluate the feasibility of using an interactive 3D home visualisation software as a tool to aid occupational therapists in carrying out pre-discharge home visits and explore the attitudes of occupational therapists toward technology in general Most therapists were not using technology with clients within their practice but recognised the need to do so Potential benefits of software for discharge planning identified: reduce cost when transporting client difficult, when the home is some distance away and when the client cannot take part in the visit Concern that software would be used to replace home visits Atwal et al (2014), UK Qualitative: think-aloud data captured while using technology and subsequent semi-structured interviews with occupational therapists Female: 57%; age, mean (SD): not reported; N ¼ 7 Occupational therapists within the UK health sector familiar with using desktop computers and typical applications…”
Section: Results Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This study design has been used by multiple usability studies in the areas of clinical and health informatics. [29][30][31] The SUS has also been used to evaluate interactive visualizations. 32,33 Since the study focused on user feedback rather than expert feedback on the dashboards, heuristic evaluation 34 was not considered.…”
Section: Study Conductionmentioning
confidence: 99%